Bitter Taste Perception of the Human Tongue Mediated by Quinine and Caffeine Impregnated Taste Strips. (August 2020) - Liu, David T.; Besser, Gerold; Oeller, Florian; Mueller, Christian A.; Renner, Bertold
Objectives: Tests for gustatory function have become increasingly important in diagnosis and treatment of patients with taste disorders. While caffeine and quinine hydrochloride solutions have been used for global testing of bitter perception, only quinine has been used to test regional bitter perception by means of taste strips. The aim of the present study was to validate caffeine impregnated taste strips as an alternative to quinine taste strips for assessment of regional bitter perception. Methods: A total of 46 healthy volunteers (mean age/range, 23/19-27 years) were included in this study. Quinine and caffeine impregnated taste strips were pairwise presented at different parts of the tongue. Perceived intensity and hedonic dislike were evaluated using labeled magnitude scales. Additionally, gustatory function was assessed using the taste strips test and overall sense of taste was rated using visual analog scales. Results: Assessment of gustatory function demonstrated scores within the normogeusic range in most included subjects (mean/SD, 13.1/2.5). Notably, equally concentrated quinine and caffeine impregnated taste strips placed on different regions of the tongue did not lead to significant differences in perceived intensity or hedonic dislike, whereas quinine and caffeine impregnated taste strips of different concentrations placed on the same region on the tongue led to significant differences of perceived intensity and hedonic dislike. Furthermore, no correlation was found between self-assessment of gustatory function and taste strips scores. Conclusion: Caffeine seems to be a valid bitter compound for regional testing using taste strips and may be used alternatively to quinine.